Narrative Concepts in the Study of Eighteenth-Century Literature - Mäkikalli, Aino; Steinby, Liisa (Crossing Boundaries: Turku Medieval and Early Modern Studies, 2017)
This collection of essays studies the encounter between allegedly ahistorical concepts of narratology and eighteenth-century literature. It questions whether the general concepts of narratology are as such applicable to historically specific fields, or whether they need further specification. Furthermore, at issue is the question whether the theoretical concepts actually are, despite their appearance of ahistorical generality, derived from the historical study of a particular period and type of literature. In the essays such concepts as genre, plot, character, event, tellability, perspective, temporality, description, reading, metadiegetic narration, and paratext are scrutinized in the context of eighteenth-century texts. The writers include some of the leading theorists of both narratology and eighteenth-century literature.